The European redemption pact: Implementation and macroeconomic effects - Hasan Doluca; Malte Hübner; Dominik Rumpf; Benjamin Weigert (Intereconomics, 2012)
One possible solution to the sovereign debt crisis is the European Redemption Pact (ERP) proposed by the German Council of Economic Experts. The ERP provides sustainable financing conditions for participating sovereigns to facilitate bringing public debt ratios below the reference value of 60% within the next 20 to 25 years. In this paper, we describe one possible way of implementing the ERP and analyse the fiscal effects of participating in the ERP. The macroeconomic impact of the proposal is illustrated with the multi-country model NiGEM.
Keywords: 330; Öffentliche Schulden; Europäische Wirtschafts- und Währungsunion; Haushaltskonsolidierung; Europäischer Stabilitätsmechanismus; Makroökonomischer Einfluss; Mehr-Länder-Modell; EU-Staaten